2005
DOI: 10.1002/mds.20501
|View full text |Cite
|
Sign up to set email alerts
|

Addiction in Parkinson's disease: Impact of subthalamic nucleus deep brain stimulation

Abstract: In Parkinson's disease, dopamine dysregulation syndrome (DDS) is characterized by severe dopamine addiction and behavioral disorders such as manic psychosis, hypersexuality, pathological gambling, and mood swings. Here, we describe the case of 2 young parkinsonian patients suffering from disabling motor fluctuations and dyskinesia associated with severe DDS. In addition to alleviating the motor disability in both patients, subthalamic nucleus (STN) deep brain stimulation greatly reduced the behavioral disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
137
1
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 219 publications
(153 citation statements)
references
References 14 publications
8
137
1
6
Order By: Relevance
“…This finding suggests that, more than dissociating between the motivation for natural reward and drugs of abuse , the STN seems to play a more complex role in the circuit of motivation. Furthermore, as HFS of the STN applied in human patients can lead to motivational effects in line with those observed after STN lesions in rats (Temel et al, 2006;Witjas et al, 2005), it would be very interesting to assess the effects of STN HFS on motivation for alcohol in patients. It may be also very critical to take into account the alcohol intake history of these Parkinsonian patients before implanting HFS electrodes.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…This finding suggests that, more than dissociating between the motivation for natural reward and drugs of abuse , the STN seems to play a more complex role in the circuit of motivation. Furthermore, as HFS of the STN applied in human patients can lead to motivational effects in line with those observed after STN lesions in rats (Temel et al, 2006;Witjas et al, 2005), it would be very interesting to assess the effects of STN HFS on motivation for alcohol in patients. It may be also very critical to take into account the alcohol intake history of these Parkinsonian patients before implanting HFS electrodes.…”
Section: Discussionmentioning
confidence: 94%
“…It is now well established that the STN is involved in cognitive and motivational behavior both in rats and monkeys (Baunez et al, 2002Robbins, 1997, 1999;Darbaky et al, 2005;Winstanley et al, 2005) and in humans (Temel et al, 2006;Witjas et al, 2005). STN lesions can differentially modulate the motivation for natural reward and drugs of abuse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The STN and mood Depression, apathy and anxiety can arise as complications after surgery [60][61][62][63] and rare cases of acute stimulationinduced depressed mood have been reported [57,58]. However, the vast majority of cases with an acute emotional response to STN DBS exhibit hypomania [50] or mania [25,52].…”
Section: The Stn and Impulsivitymentioning
confidence: 99%
“…More importantly, a systematic study of a large number of PD patients revealed a mood effect of acute STN DBS that corresponds to subjective wellbeing or euphoria, and not depression [23,59]. Single case reports have also shown that dysphoria during the off-medication period is improved by STN DBS [60][61][62]. Accumulated data from the literature is confusing on first sight, because postoperative mood outcome is influenced not only by STN DBS itself, but also by a reduction in medication, occasionally leading to a dopamine withdrawal syndrome with increases in anxiety, apathy and depression [63,64].…”
Section: The Stn and Impulsivitymentioning
confidence: 99%